The beliefs in Karma and rebirth as motivation for charitable giving: A theoretical model - Punyasavatsut, Arunee; Jongadsayakul, Woradee (Research Journal in Advanced Humanities, 2025)
This paper proposes a two-period model with consumption/donation choices to explain how religious beliefs in karma and rebirth affect donation behavior. The first period corresponds to the present life, and the second period corresponds to the next life. Solving the model’s utility maximization problem shows how an individual allocates income toward donation to receive merit in the next life and how the amount of donation is affected by factors such as incomes, heterogeneity in karmic and rebirth beliefs, heterogeneity in warm-glow preferences, and cost of donation. In addition, this paper considers the role of donation tax allowance incentive in a warm glow model. The results of theoretical models show that charitable organizations can increase donations by (1) emphasizing karma believers (2) enhancing psychological benefits from donations (3) reducing costs associated with making donations and (4) promoting tax-deductibility of the charity.